PEMAHAMAN DAN KEYAKINAN MASYARAKAT TERHADAP PENGGUNAAN TERAPI KOMPLEMENTER DALAM PERSPEKTIF BUDAYA LOKAL DAN KEPERAWATAN HOLISTIK - Sucipto, Ade; Rahayu, Sri; Kurniati, Ainun (JKM-Bid: JURNAL KESEHATAN MASYARAKAT KEBIDANAN (The Journal of Public Health Midwifery), 2025)
The use of complementary and alternative therapies has increasingly become part of community health practices, particularly in relation to local culture and belief systems. However, community understanding of complementary therapies is not always supported by evidence-based information, which may pose potential risks in their application. In the context of holistic nursing, understanding cultural beliefs and community perspectives is essential to provide safe and comprehensive care. This study aimed to explore community understanding and beliefs regarding the use of complementary therapies from a local cultural perspective. This research employed a qualitative approach with a phenomenological design. Participants were community members who had used complementary therapies and were selected using purposive sampling. Data were collected through in-depth interviews guided by semi-structured questions and analyzed thematically until data saturation was achieved. Data trustworthiness was ensured through member checking and source triangulation. The findings revealed five main themes: community knowledge of complementary therapies derived from intergenerational experiences, cultural beliefs regarding the benefits and safety of complementary therapies, the influence of social environments on decision-making, the use of complementary therapies as a complement to medical treatment, and concerns related to safety and limited access to reliable information. These findings indicate that local culture and social environments play a significant role in shaping community health practices. Therefore, nurses have a strategic role in providing culturally sensitive and evidence-based education to support holistic nursing practice and the safe use of complementary therapies.